1992
DOI: 10.1007/bf00197381
|View full text |Cite
|
Sign up to set email alerts
|

On the genetic control of the regeneration response in the dioecious Melandrium album

Abstract: Summary.Melandrium album (2n = 24), a dioecious species with heteromorphic sex chromosomes (XY, male; XX, female), has a strong genetic commitment for sex determination. So far the in vitro regeneration response in this species has appeared to be restricted to female plants. We report here a procedure for achieving active regeneration from explants and mesophyll protoplasts of selected female plants. Shoots were frequently induced in hormone-free media and in the presence of cytokinins or low concentrations (<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In vitro techniques also have been used for the propagation of several Caryophyllaceae genera. Successful establishment of Dianthus caryophyllus L. (Frey and Janick, 1991;Kim and Kang, 1986), Gypsophila paniculata L. (Han et al, 1991;Kusey et al, 1980), and Melandrium album L. (Ye et al, 1992) have been reported; however, the wild P. chartacea population is steadily declining because of reduced seed production and viability primarily due to encroaching commercial development and agricultural land use (Christman and Judd, 1990). Therefore, our objective was to develop a micropropagation protocol to produce adequate plant material for eventual reintroduction studies in landscape preservation areas.…”
mentioning
confidence: 99%
“…In vitro techniques also have been used for the propagation of several Caryophyllaceae genera. Successful establishment of Dianthus caryophyllus L. (Frey and Janick, 1991;Kim and Kang, 1986), Gypsophila paniculata L. (Han et al, 1991;Kusey et al, 1980), and Melandrium album L. (Ye et al, 1992) have been reported; however, the wild P. chartacea population is steadily declining because of reduced seed production and viability primarily due to encroaching commercial development and agricultural land use (Christman and Judd, 1990). Therefore, our objective was to develop a micropropagation protocol to produce adequate plant material for eventual reintroduction studies in landscape preservation areas.…”
mentioning
confidence: 99%